8(2x-5)-6(3x+7)=0

Simple and best practice solution for 8(2x-5)-6(3x+7)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(2x-5)-6(3x+7)=0 equation:


Simplifying
8(2x + -5) + -6(3x + 7) = 0

Reorder the terms:
8(-5 + 2x) + -6(3x + 7) = 0
(-5 * 8 + 2x * 8) + -6(3x + 7) = 0
(-40 + 16x) + -6(3x + 7) = 0

Reorder the terms:
-40 + 16x + -6(7 + 3x) = 0
-40 + 16x + (7 * -6 + 3x * -6) = 0
-40 + 16x + (-42 + -18x) = 0

Reorder the terms:
-40 + -42 + 16x + -18x = 0

Combine like terms: -40 + -42 = -82
-82 + 16x + -18x = 0

Combine like terms: 16x + -18x = -2x
-82 + -2x = 0

Solving
-82 + -2x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '82' to each side of the equation.
-82 + 82 + -2x = 0 + 82

Combine like terms: -82 + 82 = 0
0 + -2x = 0 + 82
-2x = 0 + 82

Combine like terms: 0 + 82 = 82
-2x = 82

Divide each side by '-2'.
x = -41

Simplifying
x = -41

See similar equations:

| m^3-4m^2+16m=0 | | 17x+25=14x-8 | | (6x-8)(8x^2+8x-1)= | | 3x(x^4-16)=(x^4-16) | | 5w-1=49 | | 76-2x=3x+6 | | -5y+2=-3 | | 5(4r-w)(r-4w)= | | 5*(m-5)=3*(m+1) | | 21-6x=10-8x | | (x-1)*(x+3)=5 | | 5lne^4x=80 | | 5e^4x=80 | | 7x+6x=72+x | | 3x^4=123 | | a^2-19+60=0 | | 5(x-1)=3(x+3) | | 17x^2-4x-3=0 | | 8y+9=6y-5 | | 3x-7=x+23 | | 9w-7w+5=-31 | | h+6=11 | | 4y^3=0 | | 3(4+x)=24 | | t^2+7t-2=0 | | 28x^2-20x+8=0 | | g^2+2g+0.4=0.9g^2+g | | -6x^2-5x+6=0 | | (x+5)-13=2 | | 3+x-12=20-3+8-20 | | 4x+13=3x+11 | | 30+x=17+2 |

Equations solver categories